Probing magnetization dynamics of iron oxide nanoparticles using a point-probe magneto-optical method - Wang, Xuyiling; Cabrera, David; Yang, Ying; Telling, Neil (Frontiers in Nanotechnology, 2023)
Magnetic nanoparticles (MNPs) are promising as local heat generators for magnetic hyperthermia under AC magnetic fields. The heating efficacy of MNPs is determined by the AC hysteresis loop area, which in turn is affected by the dynamic magnetic properties of the nanoparticles. Whilst inductive-based AC magnetometers can measure the average magnetic behavior of samples, the use of the magneto-optical Faraday effect with a focused laser spot allows point-probe measurements to be made, and without some of the magnetic field limitations imposed by inductive methods. In this work, the AC magnetic properties of different sized iron oxide MNPs in suspension were measured by AC magnetometry and AC susceptibility techniques. AC hysteresis loops measured by magnetooptical magnetometry were validated using a commercial inductive AC magnetometer, and compared to the magnetization relaxation behavior revealed by fitting the AC susceptibility data. The spatial sensitivity of the point-probe magneto-optical method is also demonstrated by measuring the AC hysteresis loop from large (>1 μm) MNP aggregates dried onto glass slides. These aggregated particles are found to be magnetically softer than in their suspension form, suggesting interparticle coupling mechanisms could occur when the nanoparticles form dense aggregates.